Morphological Feature Extraction with Local Histogram Equalization - Catalbas, Mehmet Cem; Issever, Didem; Gulten, Arif (Ieee, 2015)
In this work, success of image feature extraction based on morphological is examined by various histogram equalization techniques. In comparison process, traditional histogram equalization, adaptive histogram equalization and local histogram equalization methods are used. In addition to that, effects on different structure element parameters is examined success of image feature extraction process.
Yerel Histogram Eşitleme Yöntemi ile Morfolojik Öznitelik Ayriştirma
23nd Signal Processing and Communications Applications Conference (SIU) -- MAY 16-19, 2015 -- Inonu Univ, Malatya, TURKEY
Keywords: Image segmentation; local histogram equalization; feature extraction; image erosion; image dilation